Ethics and civil drones : European policies and proposals for the industry - De Miguel Molina, María; Santamarina Campos, Virginia (Springer International Publishing : Imprint : Springer, 2018)
This book is open access under a CC BY license.
Keywords: Law.; Computers.; Law and legislation.; Law of the sea.; International law.; Intellectual property.; Electronic digital computers.; Ordinateurs.; Propriété intellectuelle.; computers.; intellectual property.; Electronic digital computers; Computers; Intellectual property; International law; Law; Law of the sea